Solid-state electrolyte and surface modification method thereof, composite electrode and preparation method, and all-solid-state lithium battery
Patent Information
- Application Number
- CN202411111654.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-14
- Publication Date
- 2026-11-03
- Estimated Expiration
- 2044-08-14
AI Technical Summary
Existing sulfide and halide solid electrolytes suffer from interfacial reaction problems, narrow electrochemical windows, and incompatibility with Li+/Li+/Li+/Li+/Li+ cathode materials when matched with high-voltage cathode materials, resulting in insufficient battery energy density.
By adding perfluoropolyether compounds to an inorganic solid electrolyte and forming a surface modification layer through mechanical ball milling, the positive electrode and electrolyte are isolated, side reactions and oxidation reactions are suppressed, and the surface modification layer is formed on the surface to isolate the positive electrode and electrolyte, suppress side reactions, and prevent electrolyte oxidation under high voltage.
Stable cycling at high voltage (≥4.3 V vs Li+/Li) was achieved, improving the battery's energy density and cycle performance, maintaining the ionic conductivity of the solid electrolyte, and reducing production energy consumption.
Smart Images

Figure CN118888824B_ABST
Abstract
Description
Technical Field
[0001] This disclosure relates to the field of solid-state battery technology, and more particularly to a solid electrolyte surface modification method and its application in solid-state batteries, and more specifically to a solid electrolyte surface modification method, a solid electrolyte and a composite cathode prepared therefrom in all-solid-state lithium batteries. Background Technology
[0002] Against the backdrop of global transportation electrification, traditional lithium-ion batteries face multiple challenges, including safety, energy density, and operating temperature. All-solid-state lithium batteries, especially those using non-flammable solid electrolytes, have become a research hotspot due to their advantages such as safety, lithium metal anode compatibility, and wide operating temperature range.
[0003] However, existing sulfide solid electrolytes have high ionic conductivity, but suffer from a narrow electrochemical window and high voltage requirements (≥4.3 V vs Li) compared to LiCoO2, ternary NCM, etc. + Issues such as incompatibility with Li cathode materials exist. While halide solid electrolytes offer some improvement, their cutoff voltage only reaches approximately 4.2~4.3 V compared to Li. + / Li is insufficient to meet the demands for higher energy density. During capacity expansion by increasing the charging cutoff voltage, complex interfacial reactions between the positive electrode and electrolyte, as well as mechanical failures caused by changes in the positive electrode volume, are encountered. While existing positive electrode surface coatings can suppress side reactions between the positive electrode and electrolyte, the oxidation reaction of the electrolyte itself is not effectively suppressed, especially at higher operating voltages. Therefore, there is currently a lack of coatings that can withstand high voltages (≥4.3 V vs Li). + A solid electrolyte that is well-matched to the positive electrode material (Li). Summary of the Invention
[0004] In view of this, the main objective of this disclosure is to provide a solid electrolyte and its surface modification method, a composite electrode and its preparation method, and an all-solid-state lithium battery, in order to at least partially solve at least one of the aforementioned technical problems.
[0005] To achieve the above objectives, the technical solution disclosed herein is as follows:
[0006] In one aspect of this disclosure, a method for modifying the surface of a solid electrolyte is provided, comprising:
[0007] Under an inert atmosphere, perfluoropolyether compounds are added to an inorganic solid electrolyte and mixed by mechanical ball milling to obtain a solid electrolyte with surface modification of perfluoropolyether compounds.
[0008] In this case, the amount of perfluoropolyether compound added per gram of inorganic solid electrolyte is 5 to 200 microliters.
[0009] As a second aspect of this disclosure, a solid electrolyte modified with a perfluoropolyether compound surface, prepared by the above-described solid electrolyte surface modification method, is provided, wherein the solid electrolyte comprises:
[0010] Inorganic solid electrolyte, and a layer of perfluoropolyether compound coating on the surface of the inorganic solid electrolyte.
[0011] As a third aspect of this disclosure, a method for preparing a composite cathode is provided, comprising:
[0012] Under an inert atmosphere, the solid electrolyte, positive electrode material, and binder modified with the above-mentioned perfluoropolyether compound are mixed to obtain a composite positive electrode.
[0013] As a fourth aspect of this disclosure, a composite cathode prepared by the above-described preparation method is provided, wherein the composite cathode includes a solid electrolyte as provided in the second aspect of this disclosure, as well as a cathode material and a binder.
[0014] As another aspect of this disclosure, an all-solid-state lithium battery is provided, comprising:
[0015] The solid electrolyte provided in the second aspect of this disclosure, and the composite positive and negative electrodes provided in the fourth aspect of this disclosure are assembled together, wherein the negative electrode material is selected from lithium alloy, graphite, and silicon-based negative electrodes.
[0016] According to embodiments of this disclosure, a mechanical ball milling method is used to modify the surface of a solid electrolyte with perfluoropolyether. The modified electrolyte still maintains a high room temperature ionic conductivity (≥1 mS / cm). -1 The process is simple, has good repeatability, and requires a low ball mill speed, which reduces production energy consumption. Attached Figure Description
[0017] Figure 1 These are high-resolution transmission electron microscope images of the solid electrolyte powders prepared in Examples 1, 8 and Comparative Example 1 of this disclosure;
[0018] Figure 2 This is the electrochemical impedance spectroscopy of the solid electrolyte sheet prepared in Example 1 of this disclosure;
[0019] Figure 3 This is the electrochemical impedance spectroscopy of the solid electrolyte sheet prepared in Example 2 of this disclosure;
[0020] Figure 4 This is the electrochemical impedance spectroscopy of the solid electrolyte sheet prepared in Example 3 of this disclosure;
[0021] Figure 5This is the electrochemical impedance spectroscopy of the solid electrolyte sheet prepared in Example 4 of this disclosure;
[0022] Figure 6 This is the electrochemical impedance spectroscopy of the solid electrolyte sheet prepared in Example 5 of this disclosure;
[0023] Figure 7 This is the electrochemical impedance spectroscopy of the solid electrolyte sheet prepared in Example 6 of this disclosure;
[0024] Figure 8 This is the electrochemical impedance spectroscopy of the solid electrolyte sheet prepared in Example 7 of this disclosure;
[0025] Figure 9 This is the electrochemical impedance spectroscopy of the solid electrolyte sheet prepared in Comparative Example 1 of this disclosure;
[0026] Figure 10 This is the electrochemical impedance spectroscopy of the solid electrolyte sheet prepared in Comparative Example 2 of this disclosure;
[0027] Figure 11 This is a graph showing the electrochemical performance test results of the all-solid-state lithium battery prepared in Comparative Example 4 of this disclosure;
[0028] Figure 12 This is a graph showing the electrochemical performance test results of the all-solid-state lithium battery prepared in Example 10 of this disclosure. Detailed Implementation
[0029] To make the objectives, technical solutions, and advantages of this disclosure clearer, the following detailed description is provided in conjunction with specific embodiments.
[0030] The endpoints and any values of the ranges disclosed in this disclosure are not limited to the precise ranges or values, and such ranges or values should be understood to include values close to such ranges or values. For numerical ranges, the endpoint values of the various ranges, the endpoint values of the various ranges and individual point values, and individual point values can be combined with each other to obtain one or more new numerical ranges, which should be regarded as specifically disclosed in this disclosure.
[0031] The terminology used herein is for the purpose of describing particular embodiments only and is not intended to limit this disclosure. The terms “comprising,” “including,” etc., as used herein indicate the presence of the stated features, steps, operations, and / or components, but do not exclude the presence or addition of one or more other features, steps, operations, or components.
[0032] Existing all-solid-state lithium batteries face the challenge of increasing their operating voltage, especially for high-nickel (X) batteries. NiWith a nickel-cobalt-manganese ternary (NCM) cathode material containing ≥ 0.8%, the battery's charging cut-off voltage is increased from the standard 4.3 V vs Li + / Li increased to 4.6 V vs Li + Li₂ / Li can significantly improve battery capacity. However, most current halide-based batteries can only achieve a cutoff voltage of 4.2~4.3 V vs Li₂ / Li ... + / Li. As the cutoff voltage continues to rise, complex interfacial reactions occur between the cathode material and the halide solid electrolyte, including chemical and electrochemical reactions between the NCM and the halide solid electrolyte, as well as oxidation reactions of the halide solid electrolyte itself. These reactions lead to electrolyte structure destruction and the accumulation of decomposition products, which hinder lithium-ion transport, thus causing battery capacity decay. In addition, volume changes in the cathode material and the rigidity of the solid electrolyte can also lead to mechanical failures, especially at high voltages (≥4.3 V vs Li). + Under the condition of / Li), more lithium ion insertion and extraction causes a more significant volume change, resulting in the loss of contact between the cathode material and the solid electrolyte, thereby exacerbating mechanical failure.
[0033] In realizing the concept of this disclosure, it was discovered that current strategies often involve coating the cathode surface with various inorganic coatings to mitigate side reactions between it and the solid electrolyte. However, such strategies still face challenges in achieving high discharge capacity, superior rate performance, and excellent cycle stability. This is mainly due to two limiting factors: First, while the coating on the cathode surface can suppress side reactions between the cathode and the electrolyte, the oxidation reaction of the electrolyte itself is not effectively suppressed, especially at higher operating voltages (≥4.3 V vs Li). + This problem is even more severe under (Li) conditions. Secondly, rigid inorganic coatings have no significant effect on mitigating mechanical failures in cathode materials.
[0034] Compared to cathode surface coating strategies, surface modification of the solid electrolyte itself can isolate the electrolyte from the cathode, thereby effectively suppressing side reactions. It also has the potential to inhibit the electrolyte's own oxidation at high voltages. Perfluoropolyether compounds possess characteristics such as low surface tension, low viscosity, and higher wettability and diffusivity. These compounds are uniformly mixed into the solid electrolyte through mechanical ball milling under an inert atmosphere, forming a surface coating. This coating not only effectively isolates the solid electrolyte from the cathode material and suppresses side reactions, but also prevents oxidation of the electrolyte at high voltages (≥4.3 V vs Li) through the antioxidant properties of perfluoropolyethers. + Oxidation under ( / Li). This modification method aims to ensure that the modified solid electrolyte still possesses at least 1 mS cm⁻¹. -1The high ionic conductivity, combined with good compatibility with high-voltage cathode materials, enables all-solid-state lithium batteries to operate at 4.6 V vs Li + Stable cycling at high cutoff voltages above / Li drives battery technology toward higher energy density and safety.
[0035] According to one embodiment of this disclosure, a method for modifying the surface of a solid electrolyte is proposed, comprising:
[0036] Under an inert atmosphere, perfluoropolyether compounds are added to an inorganic solid electrolyte and mixed by mechanical ball milling to obtain a solid electrolyte with surface modification of perfluoropolyether compounds.
[0037] In this case, the amount of perfluoropolyether compound added per gram of inorganic solid electrolyte is 5 to 200 microliters.
[0038] According to embodiments of this disclosure, the surface modification of a solid electrolyte with perfluoropolyether is achieved by mechanical ball milling. The modified electrolyte still maintains a high room temperature ionic conductivity (≥1 mS / cm). -1 The process is simple, has good repeatability, and requires a low ball mill speed, which reduces production energy consumption.
[0039] According to embodiments of this disclosure, the perfluoropolyether compound is selected from one or more of perfluoropolyether carboxylic acid, perfluoropolyether methacrylate, perfluoropolyether alcohol, perfluoropolyether acyl fluoride, perfluoropolyether methyl ester, perfluoropolyether ammonium carboxylate, and polyperfluoromethyl isopropyl ether, and the molecular weight of the perfluoropolyether compound is 500~2000 g / mol. The perfluoropolyether compound does not undergo significant chemical reactions with the solid inorganic electrolyte, ensuring that it does not adversely affect the conductivity of the solid electrolyte when used as a surface modification layer material, thereby guaranteeing the stable operation of the electrochemical system. Secondly, the perfluoropolyether compound itself has good antioxidant properties; when it is coated on the outer layer of the solid electrolyte, it can effectively prevent the self-oxidation reaction of the solid electrolyte. In addition, the relatively high fluorine content in perfluoropolyether compounds means that some fluorine atoms may react with lithium ions in the inorganic solid electrolyte to form a small amount of lithium fluoride in situ. Lithium fluoride has electronic insulating properties, which can further suppress side reactions between the cathode material and the solid electrolyte, reduce unnecessary energy loss and performance degradation, and improve the overall reliability of the electrochemical system.
[0040] According to embodiments of this disclosure, the inorganic solid electrolyte is selected from Li 0.45 La 0.45 Zr 0.1 Ta 0.16 Cl3, Li 0.9 NbO 0.9 Cl 4.1, Li3InC16, Li3YC16, Li3ScC16, Li3ErC16, Li3HoC16, Li2ZrC16, Li 1.75 ZrCl 4.75 O 0.5 , Li2HfC16, LiTaCl6, LiTaOCl4, LiAlCl 2.5 O 0.75 Li 9.54 Si 1.74 P 1.44 S 11.7 Cl 0.3 Li 9.54 Si 0.6 Ge 0.4 P 1.44 S 11.1 Br 0.3 O 0.6 Li7P3S 11 The surface modification method disclosed herein is applicable to any one of the following inorganic solid electrolytes: lithium phosphorus sulfide, lithium germanium phosphorus sulfide, lithium lanthanum titanium oxide, lithium lanthanum zirconium oxide, and NASICON-type oxide. This method has broad applicability and can be effectively applied to various inorganic solid electrolytes, further improving the overall performance of solid-state batteries.
[0041] According to embodiments of this disclosure, during the mechanical ball milling process, the mass ratio of the grinding balls to the perfluoropolyether compound and the inorganic solid electrolyte is 5-50:1, for example, 5:1, 10:1, 20:1, 30:1, 50:1, etc. Preferably, the grinding balls are made of zirconium oxide material, and the grinding balls include three types with diameters of 10 mm, 8 mm, and 5 mm. Through the mechanical impact and friction of the grinding balls, the particle refinement and dispersion of the mixture can be effectively promoted, and an appropriate ball-to-material ratio ensures that the perfluoropolyether compound can be uniformly coated on the surface of the inorganic solid electrolyte. The mechanical ball milling process is carried out at a speed of 100-450 rpm, for example, 100 rpm, 200 rpm, 300 rpm, 400 rpm, 450 rpm, etc., and the time is 0.5-24 hours, for example, 0.5 hours, 1 hour, 10 hours, 20 hours, 24 hours, etc. Appropriate rotation speed and time ensure sufficient mixing energy while avoiding overheating or structural damage to the material caused by excessive rotation speed. The specific program settings for the mechanical ball milling process are as follows: the mechanical ball mill first runs forward for 2-5 minutes, allowing the material to gradually refine and mix under the impact and friction of the grinding balls; then, the machine stops running for 1-2 minutes to allow the material some relaxation time; the machine then runs in reverse for 2-5 minutes to further promote uniform mixing of the material; after that, it pauses again for 1-2 minutes. This forward-intermittent-reverse cycle not only ensures the uniformity of material mixing but also avoids overheating or mechanical wear problems caused by continuous operation, thereby improving the efficiency and safety of the entire ball milling process. In addition, mechanical ball milling is a simple and repeatable method for surface modification of solid electrolytes, requiring a relatively low ball milling speed, which effectively reduces energy consumption in the production process and enhances the economic and environmental benefits of the production process.
[0042] According to embodiments of this disclosure, a pretreatment process is included before mechanical ball milling. Specifically, the pretreatment includes placing the zirconia ball mill jar, plastic centrifuge tube, and zirconia grinding beads in a vacuum oven at 60-80°C (0.01-0.05 MPa) for 6-24 hours to ensure that all trace amounts of moisture are removed. After drying, the filling material is sealed, followed by the mechanical ball milling process.
[0043] According to embodiments of this disclosure, the mechanical ball milling mixing process is carried out under an inert atmosphere to prevent the solid electrolyte material from undergoing chemical reactions such as oxidation during the ball milling process. The inert atmosphere is high-purity argon (argon purity ≥ 99.999%) or nitrogen atmosphere (nitrogen purity ≥ 99.999%).
[0044] According to an embodiment of the second aspect of this disclosure, a solid electrolyte modified with a perfluoropolyether compound is provided, comprising: an inorganic solid electrolyte, and a perfluoropolyether compound layer coated on the surface of the inorganic solid electrolyte.
[0045] According to embodiments of this disclosure, a coating layer formed by perfluoropolyether compounds is used to modify the surface of an inorganic solid electrolyte. The perfluoropolyether compound coating layer isolates the solid electrolyte from the positive electrode material, effectively suppressing side reactions. The antioxidant properties of the perfluoropolyether compounds help prevent oxidation of the solid electrolyte in high-voltage environments (≥4.3V vs Li). + Oxidative decomposition under Li) to maintain the stability of the electrolyte structure.
[0046] According to embodiments of this disclosure, the thickness of the perfluoropolyether compound layer is 0.5~5 nm, for example, it can be 0.5 nm, 1 nm, 2 nm, 3 nm, 4 nm, 5 nm, etc. If the perfluoropolyether compound layer is too thick, it will hinder the migration path of ions, resulting in a decrease in the ionic conductivity of the solid electrolyte; if the perfluoropolyether compound layer is too thin, it is impossible to achieve complete and uniform coating of the solid electrolyte surface, and the surface modification effect of the solid electrolyte cannot be achieved.
[0047] According to embodiments of this disclosure, by controlling the thickness of the perfluoropolyether compound coating layer, the ionic conductivity of the solid electrolyte is maintained at 1 mS / cm at room temperature while preserving the structural integrity of the solid electrolyte. -1 ~5 mS cm -1 Within a certain range, the ion transport characteristics of the surface-modified solid electrolyte are guaranteed. Furthermore, the surface modification of the solid electrolyte with perfluoropolyether compounds improves the interfacial compatibility between the solid electrolyte and the high-voltage cathode material, enabling it to be matched with high voltages (≥4.3 V vs Li). + A composite cathode prepared from Li (Li) cathode material. At 4.6 V vs Li + At the cutoff voltage of / Li, surface-modified solid electrolytes can improve the specific capacity of composite cathodes and the cycle performance of batteries.
[0048] According to an embodiment of the third aspect of this disclosure, a method for preparing a composite positive electrode is provided, comprising: mixing a solid electrolyte modified with a surface of a perfluoropolyether compound, a positive electrode material, and a binder under an inert atmosphere to obtain a composite positive electrode.
[0049] According to embodiments of this disclosure, the high-voltage positive electrode material is capable of withstanding high voltage (≥4.6V vs Li) during battery charging and discharging. + The cathode material is selected from LiNi. 1 / 3 Co 1 / 3 Mn 1 / 3 O2 (NCM111), LiNi 0.5 Co 0.2 Mn 0.3O2 (NCM523), LiNi 0.6 Co 0.2 Mn 0.2 O2 (NCM622), LiNi 0.8 Co 0.1 Mn 0.1 O2 (NCM811), LiNi 0.88 Co 0.07 Mn 0.05 O2 (Ni88), LiNi 0.92 Co 0.03 Mn 0.05 O2 (Ni92), lithium cobalt oxide (LiCoO2), lithium manganese oxide (LiMn2O4), lithium nickel manganese oxide (LiNi 0.5 Mn 1.5 One of the following (O4). The binder is selected from one or more of polytetrafluoroethylene (PTFE), polyvinylidene fluoride (PVDF), polyacrylic acid (PAA), polysiloxane (PDMS), polyvinyl alcohol (PVA), polyethylene terephthalate (PET), styrene-butadiene rubber (SBR), carboxymethyl cellulose (CMC), and sodium alginate. Further, the mass ratio of the solid electrolyte, the positive electrode material, and the binder is 37~17:60~80:3, for example, it can be 37:60:3, 30:80:3, 20:70:3, 20:80:3, 17:80:3, etc. An appropriate proportion of solid electrolyte ensures that the composite cathode forms sufficient ion conduction pathways inside the battery, thereby effectively supporting the normal operation cycle of the battery. As a key component for battery energy storage and release, the high proportion of cathode material allows the composite cathode to carry more active materials, significantly improving the energy density of the battery and enabling it to store more electrical energy. An appropriate amount of binder ensures a tight connection between electrode materials, preventing detachment or pulverization during charging and discharging.
[0050] According to embodiments of this disclosure, in the preparation method of the composite cathode, the inert atmosphere is a high-purity argon atmosphere (argon purity ≥ 99.999%) or a nitrogen atmosphere (nitrogen purity ≥ 99.999%). The mixing method employs manual grinding or mechanical ball milling and oscillation, preferably using a zirconia ball mill jar for mechanical ball milling and oscillation. Specifically, the ball-to-material mass ratio during the mechanical ball milling and oscillation process is set to 10-15:1, the oscillation frequency is 300-400 times / minute, the oscillation time is 30-60 minutes, and the diameter of the zirconia ball mill beads is selected from at least one of 5 mm, 3 mm, and 2 mm.
[0051] According to embodiments of this disclosure, the process further includes a pretreatment before mechanical ball milling and oscillation mixing. Specifically, the pretreatment involves placing the zirconia ball mill jar, plastic centrifuge tube, and zirconia grinding beads in a vacuum oven at 60-80°C (0.01-0.05 MPa) for 6-24 hours to ensure that all trace amounts of moisture are removed. After drying, the packing is sealed, followed by the mechanical ball milling and oscillation mixing process.
[0052] According to an embodiment of the fourth aspect of this disclosure, a composite positive electrode prepared by the preparation method of the third aspect of this disclosure is provided, wherein the composite positive electrode includes a solid electrolyte as of the second aspect of this disclosure, as well as a positive electrode material and a binder.
[0053] According to embodiments of this disclosure, a composite cathode prepared using a solid electrolyte modified with a perfluoropolyether compound surface can be assembled into a full cell capable of operating at ≥4.6 V vs Li + Stable operation within the / Li voltage range, thereby effectively improving the capacity utilization of the positive electrode active material. At 4.6 V vs Li + At the high cutoff voltage of / Li, the battery exhibited high specific capacity and excellent cycle performance, indicating that the surface modification of perfluoropolyether compounds improved the interfacial compatibility between the solid electrolyte and the high-voltage cathode material.
[0054] According to another embodiment of this disclosure, an all-solid-state lithium battery is provided, comprising:
[0055] It is assembled from the solid electrolyte of the second aspect of this disclosure, the composite positive electrode and the negative electrode of the fourth aspect of this disclosure, wherein the negative electrode material is selected from lithium alloy, graphite and silicon-based negative electrode.
[0056] According to embodiments of this disclosure, the charge / discharge voltage of the all-solid-state lithium battery is 2.8~4.6 V vs Li + / Li, for example, could be 2.8 V vs Li + / Li、3 V vs Li + / Li, 3.5 V vs Li + / Li、4 V vs Li + / Li, 4.6 V vs Li + / Li et al.
[0057] According to embodiments of this disclosure, an all-solid-state lithium battery prepared based on a solid electrolyte modified with a perfluoropolyether compound surface achieves a performance of 4.6 V vs Li + Stable cycling can be achieved at high cutoff voltages for Li, with high voltages (4.3~4.6V vs Li). +The / Li) operating window promotes the full utilization of active materials in the cathode material, allowing its capacity to be fully released, thereby improving the overall energy density of the battery.
[0058] To make the objectives, technical solutions, and advantages of this disclosure clearer, the following detailed description is provided in conjunction with specific embodiments and accompanying drawings. Unless otherwise specified, specific techniques or conditions in the embodiments are conventional methods and can be performed according to the techniques or conditions described in the literature in this field or according to the product manual.
[0059] In this embodiment of the disclosure, the raw materials for preparing the solid electrolyte include: lithium chloride (LiCl, Shanghai Aladdin Biochemical Technology Co., Ltd., anhydrous grade, 99.9% purity), lanthanum chloride (LaCl3, Shanghai Aladdin Biochemical Technology Co., Ltd., anhydrous grade, 99.9% purity), zirconium chloride (ZrCl4, Shanghai Aladdin Biochemical Technology Co., Ltd., anhydrous grade, 99.9% purity), tantalum chloride (TaCl5, Shanghai Aladdin Biochemical Technology Co., Ltd., anhydrous grade, 99.9% purity), lithium hydroxide (LiOH, Shanghai Aladdin Biochemical Technology Co., Ltd., anhydrous grade, 99.9% purity), niobium chloride (NbCl5, Shanghai Aladdin Biochemical Technology Co., Ltd., anhydrous grade, 99.9% purity), etc.
[0060] In this embodiment of the disclosure, the perfluoropolyethers used for surface modification of the solid electrolyte include: perfluoropolyether carboxylic acid (molecular weight (MW) 500, Suzhou Cangmu New Materials Co., Ltd.), perfluoropolyether carboxylic acid (MW 1000, Shanghai Maclean Biochemical Technology Co., Ltd.), perfluoropolyether carboxylic acid (MW 2000, Shanghai Maclean Biochemical Technology Co., Ltd.), perfluoropolyether methacrylate (MW 500, Suzhou Cangmu New Materials Co., Ltd.), perfluoropolyether alcohol (MW 1000, Shanghai Maclean Biochemical Technology Co., Ltd.), perfluoropolyether acyl fluoride (MW 1000, Shanghai Maclean Biochemical Technology Co., Ltd.), and polyperfluoromethyl isopropyl ether (MW 1800, Shanghai Maclean Biochemical Technology Co., Ltd.), etc.
[0061] In this embodiment, the instruments and equipment used in the synthesis of the solid electrolyte and the surface modification of the perfluoropolyether include: a YXQM-0.4 L planetary ball mill from Changsha Miqi Instrument Equipment Co., Ltd.; the instruments and equipment used in the testing and assembly of the solid electrolyte ionic conductivity and the all-solid-state lithium battery include: an MJP-Y type ordinary cylindrical mold (Φ 10 mm) from Shanghai Xinno Instrument Equipment Co., Ltd., a YLJ-15T-LD manual tablet press from Hefei Kejing Materials Technology Co., Ltd., an MSK-SFM-12M micro vibration mixer from Hefei Kejing Materials Technology Co., Ltd., an SD-900M magnetron sputtering instrument from Beijing Boyuan Micro-Nano Technology Co., Ltd., a DH7001D electrochemical workstation from Jiangsu Donghua Analytical Instrument Co., Ltd., and a CT-4008T-5 V 20 mA-164 battery testing system from Shenzhen Xinwei Electronics Co., Ltd. The all-solid-state lithium battery assembly process is carried out in a dry, high-purity argon (argon purity ≥ 99.999%) glove box, where the oxygen and water content are both below 0.1 ppm.
[0062] Example 1:
[0063] Using perfluoropolyether carboxylic acid (MW 1000) to treat Li 0.45 La 0.45 Zr 0.1 Ta 0.16 Surface modification was performed using Cl3 (LLZTC).
[0064] Weigh 1 g of Li in a dry, argon-filled glove box. 0.45 La 0.45 Zr 0.1 Ta 0.16 Cl3 and 40 μL of perfluoropolyether carboxylic acid (MW 1000) were then transferred to a zirconia ball mill jar, and 40 g of zirconia grinding beads (8 g of 10 mm diameter grinding beads, 8 g of 8 mm diameter grinding beads, and 24 g of 5 mm diameter grinding beads) were added to the grinding jar.
[0065] After the grinding jar was tightly sealed, it was removed from the glove box and placed in a planetary ball mill (YXQM-0.4 L, Changsha Miqi Instrument Equipment Co., Ltd.) for mechanical ball milling. The rotation speed was set to 250 rpm, the time to 5 hours, and the program was set as follows: 2 minutes forward rotation, 1 minute interval, 2 minutes reverse rotation, 1 minute interval. Li-coated surfaces modified with perfluoropolyether carboxylic acid (MW 1000) were obtained. 0.45 La 0.45 Zr 0.1 Ta 0.16 Cl3 solid electrolyte powder S1 was stored in a dry argon-filled glove box.
[0066] In a dry, argon-filled glove box, the solid electrolyte powder S1 prepared in Example 1 was added to an MJP-Y type ordinary cylindrical mold (Φ 10 mm). A pressure of 300~360 MPa was applied to the mold using a YLJ-15T-LD manual tablet press. After cold pressing and holding for 3~5 minutes, the mold was removed to obtain a solid electrolyte sheet G1 with a diameter of 10 mm.
[0067] Example 2:
[0068] Using perfluoropolyether carboxylic acid (MW 2000) to treat Li 0.45 La 0.45 Zr 0.1 Ta 0.16 Cl3 is used for surface modification.
[0069] Weigh 1 g of Li in a dry, argon-filled glove box. 0.45 La 0.45 Zr 0.1 Ta 0.16 Cl3 and 40 μL of perfluoropolyether carboxylic acid (MW 2000) were then transferred to a zirconia ball mill jar, and 40 g of zirconia grinding beads (8 g of 10 mm diameter grinding beads, 8 g of 8 mm diameter grinding beads, and 24 g of 5 mm diameter grinding beads) were added to the grinding jar.
[0070] After the grinding jar was tightly sealed, it was removed from the glove box and placed in a planetary ball mill (YXQM-0.4 L, Changsha Miqi Instrument Equipment Co., Ltd.) for mechanical ball milling. The rotation speed was set to 250 rpm, the time to 5 hours, and the program was set as follows: 2 minutes forward rotation, 1 minute interval, 2 minutes reverse rotation, 1 minute interval. Li-coated surfaces modified with perfluoropolyether carboxylic acid (MW 2000) were obtained. 0.45 La 0.45 Zr 0.1 Ta 0.16 Cl3 solid electrolyte powder S2 was stored in a dry argon-filled glove box.
[0071] In a dry, argon-filled glove box, the solid electrolyte powder S2 prepared in Example 2 was added to an MJP-Y type ordinary cylindrical mold (Φ 10 mm). A pressure of 300~360 MPa was applied to the mold using a YLJ-15T-LD manual tablet press. After cold pressing and holding for 3~5 minutes, the mold was removed to obtain a solid electrolyte sheet G2 with a diameter of 10 mm.
[0072] Example 3:
[0073] Using perfluoropolyether alcohol (MW 1000) to treat Li 0.45 La 0.45 Zr0.1 Ta 0.16 Cl3 is used for surface modification.
[0074] Weigh 1 g of Li in a dry, argon-filled glove box. 0.45 La 0.45 Zr 0.1 Ta 0.16 Cl3 and 40 μL of perfluorinated polyether alcohol (MW 1000) were then transferred to a zirconia ball mill jar, and 40 g of zirconia grinding beads (8 g of 10 mm diameter grinding beads, 8 g of 8 mm diameter grinding beads, and 24 g of 5 mm diameter grinding beads) were added to the grinding jar.
[0075] After the grinding jar was tightly sealed, it was removed from the glove box and placed in a planetary ball mill (YXQM-0.4 L, Changsha Miqi Instrument Equipment Co., Ltd.) for mechanical ball milling. The rotation speed was set to 250 rpm, the time to 5 hours, and the program was set as follows: 2 minutes forward rotation, 1 minute interval, 2 minutes reverse rotation, 1 minute interval. Li-coated surfaces modified with perfluoropolyether alcohol (MW 1000) were obtained. 0.45 La 0.45 Zr 0.1 Ta 0.16 Cl3 solid electrolyte powder S3 was stored in a dry argon-filled glove box.
[0076] In a dry, argon-filled glove box, the solid electrolyte powder S3 prepared in Example 3 was added to an MJP-Y type ordinary cylindrical mold (Φ 10 mm). A pressure of 300~360 MPa was applied to the mold using a YLJ-15T-LD manual tablet press. After cold pressing and holding for 3~5 minutes, the mold was removed to obtain a solid electrolyte sheet G3 with a diameter of 10 mm.
[0077] Example 4:
[0078] Using perfluoropolyether fluoride (MW 1000) to treat Li 0.45 La 0.45 Zr 0.1 Ta 0.16 Cl3 is used for surface modification.
[0079] Weigh 1 g of Li in a dry, argon-filled glove box. 0.45 La 0.45 Zr 0.1 Ta 0.16 Cl3 and 40 μL of perfluoropolyether fluoride (MW 1000) were then transferred to a zirconia ball mill jar, and 40 g of zirconia grinding beads (8 g of 10 mm diameter grinding beads, 8 g of 8 mm diameter grinding beads, and 24 g of 5 mm diameter grinding beads) were added to the grinding jar.
[0080] After the grinding jar was tightly sealed, it was removed from the glove box and placed in a planetary ball mill (YXQM-0.4 L, Changsha Miqi Instrument Equipment Co., Ltd.) for mechanical ball milling. The rotation speed was set to 250 rpm, the time to 5 hours, and the program was set as follows: 2 minutes forward rotation, 1 minute interval, 2 minutes reverse rotation, 1 minute interval. This yielded Li-coated surfaces modified with perfluoropolyether fluoride (MW 1000). 0.45 La 0.45 Zr 0.1 Ta 0.16 Cl3 solid electrolyte powder S4 was stored in a dry argon-filled glove box.
[0081] In a dry, argon-filled glove box, the solid electrolyte powder S4 prepared in Example 4 was added to an MJP-Y type ordinary cylindrical mold (Φ 10 mm). A pressure of 300~360 MPa was applied to the mold using a YLJ-15T-LD manual tablet press. After cold pressing and holding for 3~5 minutes, the mold was removed to obtain a solid electrolyte sheet G4 with a diameter of 10 mm.
[0082] Example 5:
[0083] Using poly(perfluoromethyl isopropyl ether) (MW 1800) for Li 0.45 La 0.45 Zr 0.1 Ta 0.16 Cl3 is used for surface modification.
[0084] Weigh 1 g of Li in a dry, argon-filled glove box. 0.45 La 0.45 Zr 0.1 Ta 0.16 Cl3 and 40 μL of poly(perfluoromethyl isopropyl ether) (MW 1800) were then transferred to a zirconia ball mill jar, and 40 g of zirconia grinding beads (8 g of 10 mm diameter grinding beads, 8 g of 8 mm diameter grinding beads, and 24 g of 5 mm diameter grinding beads) were added to the grinding jar.
[0085] After the grinding jar was tightly sealed, it was removed from the glove box and placed in a planetary ball mill (YXQM-0.4 L, Changsha Miqi Instrument Equipment Co., Ltd.) for mechanical ball milling. The rotation speed was set to 250 rpm, the time to 5 hours, and the program was set as follows: 2 minutes forward rotation, 1 minute interval, 2 minutes reverse rotation, 1 minute interval. Li-modified poly(perfluoromethyl isopropyl ether) (MW 1800) surface was obtained. 0.45 La 0.45 Zr 0.1 Ta 0.16Cl3 solid electrolyte powder S5 was stored in a dry argon-filled glove box.
[0086] In a dry, argon-filled glove box, the solid electrolyte powder S5 prepared in Example 5 was added to an MJP-Y type ordinary cylindrical mold (Φ 10 mm). Using a YLJ-15T-LD manual tablet press, a pressure of 300~360 MPa was applied to the mold. After cold pressing and holding for 3~5 minutes, the mold was removed to obtain a solid electrolyte sheet G5 with a diameter of 10 mm.
[0087] Example 6:
[0088] Using perfluoropolyether carboxylic acid (MW 1000) to treat Li 0.9 NbO 0.9 Cl 4.8 (LNOC) is used for surface modification.
[0089] Weigh 1 g of Li in a dry, argon-filled glove box. 0.9 NbO 0.9 Cl 4.8 Add 40 μL of perfluoropolyether carboxylic acid (M.W1000) and then transfer it to a zirconia ball mill jar. Add 40 g of zirconia grinding beads (8 g of 10 mm diameter grinding beads, 8 g of 8 mm diameter grinding beads, and 24 g of 5 mm diameter grinding beads) to the grinding jar.
[0090] After the grinding jar was tightly sealed, it was removed from the glove box and placed in a planetary ball mill (YXQM-0.4 L, Changsha Miqi Instrument Equipment Co., Ltd.) for mechanical ball milling. The rotation speed was set to 250 rpm, the time to 5 hours, and the program was set as follows: 2 minutes forward rotation, 1 minute interval, 2 minutes reverse rotation, 1 minute interval. Li-coated surfaces modified with perfluoropolyether carboxylic acid (MW 1000) were obtained. 0.9 NbO 0.9 Cl 4.8 Solid electrolyte powder S6 was stored in a dry, argon-filled glove box.
[0091] In a dry, argon-filled glove box, the solid electrolyte powder S6 prepared in Example 6 was added to an MJP-Y type ordinary cylindrical mold (Φ 10 mm). A pressure of 300~360 MPa was applied to the mold using a YLJ-15T-LD manual tablet press. After cold pressing and holding for 3~5 minutes, the mold was removed to obtain a solid electrolyte sheet G6 with a diameter of 10 mm.
[0092] Example 7:
[0093] Using perfluoropolyether alcohol (MW 2000) to treat Li 0.9 NbO0.9 Cl 4.8 Perform surface finishing.
[0094] Weigh 1 g of Li in a dry, argon-filled glove box. 0.9 NbO 0.9 Cl 4.8 Add 40 μL of perfluoropolyether alcohol (M.W2000) and then transfer it to a zirconia ball mill jar. Add 40 g of zirconia grinding beads (8 g of 10 mm diameter grinding beads, 8 g of 8 mm diameter grinding beads, and 24 g of 5 mm diameter grinding beads) to the grinding jar.
[0095] After the grinding jar was tightly sealed, it was removed from the glove box and placed in a planetary ball mill (YXQM-0.4 L, Changsha Miqi Instrument Equipment Co., Ltd.) for mechanical ball milling. The rotation speed was set to 250 rpm, the time to 5 hours, and the program was set as follows: 2 minutes forward rotation, 1 minute interval, 2 minutes reverse rotation, 1 minute interval. Li-coated surfaces modified with perfluoropolyether alcohol (MW 2000) were obtained. 0.9 NbO 0.9 Cl 4.8 Solid electrolyte powder S8 was stored in a dry argon-filled glove box.
[0096] In a dry, argon-filled glove box, the solid electrolyte powder S7 prepared in Example 7 was added to an MJP-Y type ordinary cylindrical mold (Φ 10 mm). Using a YLJ-15T-LD manual tablet press, a pressure of 300~360 MPa was applied to the mold. After cold pressing and holding for 3~5 minutes, the mold was removed to obtain a solid electrolyte sheet G7 with a diameter of 10 mm.
[0097] Example 8
[0098] Using perfluoropolyether carboxylic acid (MW 1000) to treat Li 0.45 La 0.45 Zr 0.1 Ta 0.16 Cl3 is used for surface modification.
[0099] Weigh 1 g of Li in a dry, argon-filled glove box. 0.45 La 0.45 Zr 0.1 Ta 0.16 Cl3 and 80 μL of perfluoropolyether carboxylic acid (MW 1000) were then transferred to a zirconia ball mill jar, and 40 g of zirconia grinding beads (8 g of 10 mm diameter grinding beads, 8 g of 8 mm diameter grinding beads, and 24 g of 5 mm diameter grinding beads) were added to the grinding jar.
[0100] After the grinding jar was tightly sealed, it was removed from the glove box and placed in a planetary ball mill (YXQM-0.4 L, Changsha Miqi Instrument Equipment Co., Ltd.) for mechanical ball milling. The rotation speed was set to 250 rpm, the time to 5 hours, and the program was set as follows: 2 minutes forward rotation, 1 minute interval, 2 minutes reverse rotation, 1 minute interval. Li-coated surfaces modified with perfluoropolyether carboxylic acid (MW 1000) were obtained. 0.45 La 0.45 Zr 0.1 Ta 0.16 Cl3 solid electrolyte powder S8 was stored in a dry argon-filled glove box.
[0101] Comparative Example 1:
[0102] Comparative Example 1 is Li used directly without surface modification. 0.45 La 0.45 Zr 0.1 Ta 0.16 Cl3 solid electrolyte powder D1.
[0103] In a dry, argon-filled glove box, the solid electrolyte powder D1 from Comparative Example 1 was added to an MJP-Y type ordinary cylindrical mold (Φ 10 mm). Using a YLJ-15T-LD manual tablet press, a pressure of 300~360 MPa was applied to the mold. After cold pressing and holding for 3~5 minutes, the mold was removed to obtain a solid electrolyte tablet D-G1 with a diameter of 10 mm.
[0104] Comparative Example 2:
[0105] Comparative Example 2 is Li used directly without surface modification. 0.9 NbO 0.9 Cl 4.8 Solid electrolyte powder D2.
[0106] In a dry, argon-filled glove box, the solid electrolyte powder D2 from Comparative Example 2 was added to an MJP-Y type ordinary cylindrical mold (Φ 10 mm). Using a YLJ-15T-LD manual tablet press, a pressure of 300~360 MPa was applied to the mold. After cold pressing and holding for 3~5 minutes, the mold was removed to obtain a solid electrolyte tablet D-G2 with a diameter of 10 mm.
[0107] Figure 1 These are high-resolution transmission electron microscope (TEM) images of the solid electrolyte powders prepared in Examples 1, 8 and Comparative Example 1 of this disclosure.
[0108] like Figure 1As shown, the surface-modified solid electrolyte powder has a blurred band around its surface, which is a coating layer formed by perfluoropolyether compounds. The thickness of the coating layer increases with the increase in the amount of perfluoropolyether compound added. The unmodified solid electrolyte powder shows a clear outline and has no additional coating layer.
[0109] The solid electrolyte sheets G1-7 and D-G1-2 prepared in Examples 1-7 and Comparative Examples 1-2 were subjected to gold sputtering on both sides in an SD-900M magnetron sputtering system, and their ionic conductivity was tested using a DH7001D electrochemical workstation. The test frequency was 8 MHz to 1 Hz, and the applied bias voltage was 100 mV.
[0110] Figure 2 This is the electrochemical impedance spectroscopy of the solid electrolyte sheet prepared in Example 1 of this disclosure.
[0111] Figure 3 This is the electrochemical impedance spectroscopy of the solid electrolyte sheet prepared in Example 2 of this disclosure.
[0112] Figure 4 This is the electrochemical impedance spectroscopy of the solid electrolyte sheet prepared in Example 3 of this disclosure.
[0113] Figure 5 This is the electrochemical impedance spectroscopy of the solid electrolyte sheet prepared in Example 4 of this disclosure.
[0114] Figure 6 This is the electrochemical impedance spectroscopy of the solid electrolyte sheet prepared in Example 5 of this disclosure.
[0115] Figure 7 This is the electrochemical impedance spectroscopy of the solid electrolyte sheet prepared in Example 6 of this disclosure.
[0116] Figure 8 This is the electrochemical impedance spectroscopy of the solid electrolyte sheet prepared in Example 7 of this disclosure.
[0117] Figure 9 This is the electrochemical impedance spectroscopy of the solid electrolyte sheet prepared in Comparative Example 1 of this disclosure.
[0118] Figure 10 This is the electrochemical impedance spectroscopy of the solid electrolyte sheet prepared in Comparative Example 2 of this disclosure.
[0119] like Figures 2-10 As shown, the horizontal axis represents the real impedance, and the vertical axis represents the imaginary impedance. It can be observed that the ionic conductivity of the unmodified solid electrolyte sheet can reach 7.14 mS / cm. -1The surface-modified solid electrolyte sheet exhibits a slight decrease in ionic conductivity due to the formation of a perfluoropolyether compound coating, which hinders lithium-ion transport. However, the conductivity remains within the range of 1–5 mS / cm. -1 Within the range.
[0120] Example 9:
[0121] Based on the perfluoropolyether carboxylic acid (MW 1000) surface-modified Li from Example 1 0.45 La 0.45 Zr 0.1 Ta 0.16 A composite cathode was prepared using Cl3 solid electrolyte powder S1.
[0122] In a dry, argon-filled glove box, the solid electrolyte powder S1 prepared in Example 1 was mixed with high-voltage cathode material Ni88 and PTFE binder at a ratio of 37:60:3 and manually ground for 10 minutes. Then, it was mechanically vibrated for 30 minutes using a micro-vibration mixer (MSK-SFM-12M, Hefei Kejing Materials Technology Co., Ltd.), with a ball-to-material mass ratio of 10:1 (the zirconia grinding beads included both 5 mm and 3 mm diameter beads) and a vibration frequency of 300 times / minute. A uniformly mixed composite cathode powder Z1 was obtained and stored in a dry, argon-filled glove box.
[0123] Comparative Example 3:
[0124] Based on the unmodified Li in Comparative Example 1 0.45 La 0.45 Zr 0.1 Ta 0.16 A composite cathode was prepared using Cl3 solid electrolyte powder D1.
[0125] In a dry, argon-filled glove box, the solid electrolyte powder D1 from Comparative Example 1 was mixed with the high-voltage cathode material Ni88 and PTFE binder at a ratio of 37:60:3 and manually ground for 10 minutes. Then, it was mechanically vibrated for 30 minutes using a micro-vibration mixer (MSK-SFM-12M, Hefei Kejing Materials Technology Co., Ltd.). The ball-to-material mass ratio for mechanical vibration was 10:1 (the zirconia grinding beads included both 5 mm and 3 mm diameter beads), and the vibration frequency was 300 times / minute. A uniformly mixed composite cathode powder Z2 was obtained and stored in a dry, argon-filled glove box.
[0126] Example 10:
[0127] All-solid-state lithium batteries were prepared based on the composite cathode powder Z1 in Example 9.
[0128] First, 130 mg of the solid electrolyte powder S1 prepared in Example 1 was placed into a polyetheretherketone (PEEK) cylindrical mold with a diameter of 10 mm, and pressed under a pressure of 1.5 tons for 2 minutes to form a solid electrolyte layer. Then, 5 mg of the composite cathode powder Z1 prepared in Example 9 was evenly spread on the surface of the solid electrolyte layer, and pressed under a pressure of 2 tons for another 2 minutes to obtain a composite layer of solid electrolyte and cathode material. Then, a lithium indium alloy layer (lithium indium mass ratio of 1:50) was placed on the solid electrolyte layer side of the composite layer. Finally, the composite layer and the lithium indium alloy layer were placed in a custom stainless steel mold (Ningbo Zhengli New Energy Technology Co., Ltd.), and a pressure of 100 MPa was continuously applied for 24 hours to obtain an all-solid-state lithium battery C1. All the above preparation processes were performed in an argon-filled glove box.
[0129] Comparative Example 4:
[0130] All-solid-state lithium batteries were prepared based on the composite cathode powder Z1 in Comparative Example 3.
[0131] First, 130 mg of solid electrolyte powder D1 from Comparative Example 1 was placed into a 10 mm diameter polyetheretherketone (PEEK) cylindrical mold and pressed for 2 minutes under a pressure of 1.5 tons to form a solid electrolyte layer. Then, 5 mg of composite cathode powder Z2 prepared in Comparative Example 3 was evenly spread onto the surface of the solid electrolyte layer and pressed for another 2 minutes under a pressure of 2 tons to obtain a composite layer of solid electrolyte and cathode material. Next, a lithium-indium alloy layer (lithium-indium mass ratio of 1:50) was placed on the solid electrolyte layer side of the composite layer. Finally, the composite layer and the lithium-indium alloy layer were placed together in a custom stainless steel mold (Ningbo Zhengli New Energy Technology Co., Ltd.) and a pressure of 100 MPa was continuously applied for 24 hours to obtain an all-solid-state lithium battery C2. All the above preparation processes were performed in an argon-filled glove box.
[0132] Electrochemical tests were performed on the prepared all-solid-state lithium batteries C1 and C2 using a CT-4008T-5 V 20 mA-164 battery testing system. During the tests, the applied current density ranged from 0.1 to 0.2 mA cm⁻¹. -2 The charge / discharge voltage range is 2.8~4.6 V vs Li + / Li.
[0133] Figure 11 This is a graph showing the electrochemical performance test results of the all-solid-state lithium battery prepared in Comparative Example 4 of this disclosure.
[0134] Figure 12 This is a graph showing the electrochemical performance test results of the all-solid-state lithium battery prepared in Example 10 of this disclosure.
[0135] like Figures 11-12As shown, it can be observed that the all-solid-state lithium battery prepared in Example 10, compared with the all-solid-state lithium battery prepared in Comparative Example 4, exhibits better performance in the 2.8~4.6 V vs Li + Within the / Li charge / discharge voltage range, it exhibits high specific capacity and excellent battery cycle performance. The capacity retention rate after 100 cycles reaches 81.79%, indicating that the surface modification with perfluoropolyether compounds improves the interfacial compatibility between the solid electrolyte and the high-voltage cathode material, thereby enhancing battery stability and cycle life.
[0136] The specific embodiments described above further illustrate the purpose, technical solutions, and beneficial effects of this disclosure. It should be understood that the above descriptions are merely specific embodiments of this disclosure and are not intended to limit this disclosure. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of this disclosure should be included within the protection scope of this disclosure.
Claims
1. A solid electrolyte, comprising: An inorganic solid electrolyte, and a perfluoropolyether compound layer coated on the surface of the inorganic solid electrolyte, wherein the solid electrolyte is obtained through surface modification and has an ionic conductivity of 1 mS / cm at room temperature. -1 ~5 mScm -1 The surface modification method for the solid electrolyte includes: Under an inert atmosphere, perfluoropolyether compounds are added to an inorganic solid electrolyte and mixed by mechanical ball milling to obtain a solid electrolyte with surface modification of perfluoropolyether compounds. In each gram of the inorganic solid electrolyte, the amount of the perfluoropolyether compound added is 5-200 microliters. The perfluoropolyether compound is selected from one or more of perfluoropolyether carboxylic acid, perfluoropolyether methacrylate, perfluoropolyether alcohol, perfluoropolyether acyl fluoride, perfluoropolyether methyl ester, perfluoropolyether ammonium carboxylate, and polyperfluoromethyl isopropyl ether, and the molecular weight of the perfluoropolyether compound is 500~2000 g / mol. The inorganic solid electrolyte is selected from Li 0.45 La 0.45 Zr 0.1 Ta 0.16 Cl3, Li 0.9 NbO 0.9 Cl 4.1 , Li3InC16, Li3YC16, Li3ScC16, Li3ErC16, Li3HoC16, Li2ZrC16, Li 1.75 ZrCl 4.75 O 0.5 , Li2HfC16, LiTaCl6, LiTaOCl4, LiAlCl 2.5 O 0.75 Li 9.54 Si 1.74 P 1.44 S 11.7 Cl 0.3 Li 9.54 Si 0.6 Ge 0.4 P 1.44 S 11.1 Br 0.3 O 0.6 Li7P3S 11 Any one of the following inorganic solid electrolytes: lithium phosphorus sulfide, lithium germanium phosphorus sulfide, lithium lanthanum titanium oxide, lithium lanthanum zirconium oxide, and NASICON-type oxide.
2. The solid electrolyte according to claim 1, wherein: During the mechanical ball milling process, the total mass ratio of the milling beads to the perfluoropolyether compound and the inorganic solid electrolyte is 5~50:1; The mechanical ball milling process involves a rotation speed of 100-450 rpm and a time of 0.5-24 hours.
3. The solid electrolyte according to claim 1, wherein, The thickness of the perfluoropolyether compound layer is 0.5~5nm.
4. A method for preparing a composite positive electrode, comprising: Under an inert atmosphere, the solid electrolyte, positive electrode material, and binder as described in any one of claims 1 to 3 are mixed to obtain a composite positive electrode.
5. The preparation method according to claim 4, wherein: The cathode material is selected from LiNi. 1 / 3 Co 1 / 3 Mn 1 / 3 O2, LiNi 0.5 Co 0.2 Mn 0.3 O2, LiNi 0.6 Co 0.2 Mn 0.2 O2, LiNi 0.8 Co 0.1 Mn 0.1 O2, LiNi 0.88 Co 0.07 Mn 0.05 O2, LiNi 0.92 Co 0.03 Mn 0.05 One of O2, lithium cobalt oxide, lithium manganese oxide, and lithium nickel manganese oxide; The adhesive is selected from one or more of polytetrafluoroethylene, polyvinylidene fluoride, polyacrylic acid, polysiloxane, polyvinyl alcohol, polyethylene terephthalate, styrene-butadiene rubber, carboxymethyl cellulose, and sodium alginate. The mass ratio of the solid electrolyte, positive electrode material and binder is 37~17:60~80:
3.
6. Composite cathode, wherein, The composite cathode includes a solid electrolyte as described in any one of claims 1 to 3, as well as a cathode material and a binder.
7. An all-solid-state lithium battery, comprising: The electrode is assembled from the solid electrolyte of any one of claims 1 to 3, the composite positive electrode and the negative electrode of claim 6, wherein the negative electrode material is selected from lithium alloy, graphite and silicon-based negative electrode.
8. The all-solid-state lithium battery according to claim 7, wherein, The charge / discharge voltage of the all-solid-state lithium battery is 2.8~4.6 V vs Li + / Li.
Citation Information
Patent Citations
Coated sulfide solid electrolyte material and preparation method and application thereof
CN114512710A
Surface modified solid electrolyte, preparation method thereof and solid-state battery
CN117895062A
Secondary battery
WO2023243721A1
